Resposta :
Resposta:
[tex]\textsf{Leia abaixo}[/tex]
Explicação passo a passo:
[tex]\mathsf{\dfrac{3-x}{x} = 3\left(\dfrac{\sqrt{13} + 3}{6}\right)}[/tex]
[tex]\mathsf{\dfrac{3-x}{x} = \left(\dfrac{\sqrt{13} + 3}{2}\right)}[/tex]
[tex]\mathsf{6-2x = x\sqrt{13} + 3x}[/tex]
[tex]\mathsf{6 = x\sqrt{13} + 5x}[/tex]
[tex]\mathsf{6 = x(\sqrt{13} + 5)}[/tex]
[tex]\mathsf{x = \dfrac{6}{\sqrt{13} + 5}}[/tex]
[tex]\mathsf{x = \left(\dfrac{6}{\sqrt{13} + 5}\right) \times \left(\dfrac{\sqrt{13} - 5}{\sqrt{13} - 5}\right)}[/tex]
[tex]\mathsf{x = \dfrac{6\sqrt{13} - 30}{13 - 25}}[/tex]
[tex]\mathsf{x = -\dfrac{6\sqrt{13} - 30}{12}}[/tex]
[tex]\boxed{\boxed{\mathsf{x = \dfrac{5 - \sqrt{13}}{2}}}}[/tex]